Penyuluhan Penentuan Harga Pokok Produksi (HPP) pada Pelaku UMKM di Desa Kampung Anyar - Kurnia Riesty Utami; Arif Rahman Hakim; Karisma Nahliyatul Karomah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Community service activities are carried out by higher education educators as tri dharma activities. This service activity was carried out in Kampung Anyar Village. The village community of Kampung Anyar has a lot of business. This is done by the village government in creating an independent and prosperous society. This is evidenced by the large number of people who are entrepreneurs in Kampung Anyar village. Business actors carry out innovation and creativity in utilizing the surrounding natural resources by processing them into products that have a selling value. Apart from that, it also takes advantage of the condition of the area where the area has many tourism sites that have the potential to increase economic income. Many business actors still lack knowledge regarding the cost of production. So that business actors are less than the maximum actual profit. Community service activities are carried out by providing material by resource persons through delivering material, then practicing calculating the cost of production and providing insight into the importance of carrying out systematic recording in the process of business continuity. Community service activities are carried out by sorting out raw material costs, direct labor costs & indirect labor costs along with overhead costs. Systematic and simple recording is one of the successes in determining the cost of production of each product. Business actors are expected to continue to apply it in their business and attend training on an ongoing basis in understanding the determination of the cost of production.